2014
DOI: 10.1089/ars.2013.5340
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate-Prone R120GCRYAB Triggers Multifaceted Modifications of the Thioredoxin System

Abstract: Aims: The human mutation R120G in the aB-crystallin (CRYAB) causes a multisystemic disease that is characterized by hypertrophic cardiomyopathy and cytoplasmic protein aggregates. In transgenic mice, human R120GCRYAB (hR120GTg) expression in heart sequentially modifies the REDOX status, in part by the activation of the nuclear factor, erythroid derived 2, like 2 (Nrf2). Thioredoxin system (TS) components are NRF2 target genes, so it could be hypothesized that TS was affected in hR120GTg mice. Results: Transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In these mice, both reduced Trx1 and TrxR1 are upregulated through Nrf2 activation and prevent accumulation of cytoplasmic protein aggregates. This finding is of interest because it has been suggested that protein aggregates are formed due to reductive stress in desmin-related myopathy [66]. The fact that an antioxidant mechanism can reduce protein aggregates even in the presence of reductive stress conditions indicates that the protective effect of the Trx1 system may be compartmentalized.…”
Section: Role Of Trx1 In the Heart In Vivomentioning
confidence: 86%
“…In these mice, both reduced Trx1 and TrxR1 are upregulated through Nrf2 activation and prevent accumulation of cytoplasmic protein aggregates. This finding is of interest because it has been suggested that protein aggregates are formed due to reductive stress in desmin-related myopathy [66]. The fact that an antioxidant mechanism can reduce protein aggregates even in the presence of reductive stress conditions indicates that the protective effect of the Trx1 system may be compartmentalized.…”
Section: Role Of Trx1 In the Heart In Vivomentioning
confidence: 86%
“…RNA was first retro-transcribed using iScript cDNA Synthesis kit (Bio-Rad, Hercules, CA), and then either real-time PCR was carried out using iTaq SYBR Green Master Mix (Bio-Rad). The comparative C t (2 −ΔΔ C T ) method [74] was used to calculate the relative abundance of the mRNA and compared with that of housekeeping gene expression 18S rRNA as previously described [75]. For end point PCR, RNA was isolated, retro-transcribed into cDNA and then amplified using 2× Taq polemerase (NEB) and primers.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation was performed using with Agarose A/G beads (SCBT-2003), and cell lystaes or immunoprecipitates were separated by SDS-PAGE and Western immunoblotting analysis was performed using standard protocol as described previously [75]. When required, DNASE1 (Sigma) digestion was done during immunoprecipitation with 150U and 250U DNASE1.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysis, immunoprecipitation (IP), and immunoblotting were performed and quantified as described previously (16).…”
Section: Methodsmentioning
confidence: 99%